Cybersecurity Investments Decision Support Under Economic Aspects - Beissel, Stefan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book offers readers essential orientation on cybersecurity safeguards, and first and foremost helps them find the right balance between financial expenditures and risk mitigation. This is achieved by pursuing a multi-disciplinary approach that combines well-founded methods from economics and the computer sciences. Established decision making techniques are embedded into a walk-through for the complete lifecycle of cybersecurity investments. Insights into the economic aspect of the costs and benefits of cybersecurity are supplemented by established and innovative economic indicators. Readers will find practical tools and techniques to support reasonable decision making in cybersecurity investments. Further, they will be equipped to encourage a common understanding using economic aspects, and to provide cost transparency for the senior management.
Introduction -- Foundations of Cybersecurity -- Cybersecurity Safeguards -- Economic Aspects -- Foundations of Decision Making -- Lifecycle of Cybersecurity Investments -- Summary.
Keywords: Business; Management; Industrial management; Operations research; Decision making; Information technology; Business -- Data processing; Computer security; Business and Management; IT in Business; Systems and Data Security; Innovation/Technology Management; Operation Research/Decision Theory; Electronic books